Nanoporous germanium prepared by a mechanochemical reaction with enhanced lithium storage properties. Issue 8 (3rd February 2022) - Liu, Xianyu; Zhang, Qianliang; Zhu, Yansong; Xu, Shengjie; Zhang, Jia; Zheng, Yanping; Zhang, Lei; Ma, Mingguang; Rao, Honghong; Liu, Zheng
Abstract : Nanoporous Z–Ge was fabricated via a mechanochemical reaction with Mg2 Ge and ZnCl2, exhibiting long-term cycling stability in Li-ion batteries. Abstract : The cost-effective and facile fabrication of nanostructured germanium for lithium-ion batteries (LIBs) remains a grand challenge. Herein, nanoporous Z–Ge was generated via a facile two-step mechanochemical-etching reaction with Mg2 Ge and ZnCl2 . The prepared nanoporous Ge nanoparticles, as the anode for Li–Ge half cells, showed superior LIB performance, in terms of a high capacity, good rate capability, and good long-term stability of 700 cycles. Significantly, the mechanochemical reaction was extended to produce other nanoporous Ge or Si materials such as A–Ge, Z–Si, and A–Si via the mechanochemical reaction between Mg2 Ge and AlCl3, Mg2 Si and ZnCl2, and Mg2 Si and AlCl3 .